Do Employees Care about their Relative Position? Behavioural Evidence Focusing on Performance - Benno Torgler; Markus Schaffner; Sascha L. Schmidt; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Do employees care about their relative (economic) position among co-workers in an organization? And if so, does it raise or lower their performance? Behavioral evidence on these important questions is rare. This paper takes a novel approach to answering these questions, working with sports data from two different disciplines, basketball and soccer. These sports tournaments take place in a controlled environment defined by the rules of the game. We find considerable support that positional concerns and envy reduce individual performance. In contrast, there does not seem to be any tolerance for income disparity, based on the hope that such differences signal that better times are under way. Positive behavioral consequences are observed for those who are experiencing better times.
Keywords: D00; D60; L83; 330; Relative income; positional concerns; envy; social comparison; relative derivation; performance